Komodifikasi Dalam Pengembangan Tradisi Okokan Sebagai Atraksi Wisata di Desa Kediri, Tabanan - Wayan Windutama; I Nyoman Sunarta; NMS Wijaya (JURNAL MASTER PARIWISATA, 2020)
This study aims to determine the forms of commodification in the development of the Okokan tradition as a tourist attraction in Kediri Village, Tabanan. The method used in this research is descriptive qualitative data collection techniques through observation, interviews, documentation, and literature study using a ladder of citizen participation theory, product life cycle theory, and commodification theory. This study found that the level of community participation was in the form of consultation with participation between the community and the government still being passive. While the stages of developing the Okokan tradition are at a stage of growth, where the wider community is getting to know Okokan with promotions carried out and proven by the appearance of the Okokan at various events. The forms of commodification in the development of the Okokan tradition as tourist attractions include the processes of production, distribution, and consumption. Keywords: Community Participation, Okokan Tradition, Commodification, Kediri-Tabanan Village